2014
DOI: 10.1177/0022034514557671
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hypoxia on the Immunomodulatory Properties of Human Gingiva–Derived Mesenchymal Stem Cells

Abstract: The environment of bone marrow mesenchymal stem cells (MSCs) is hypoxic, which plays an important role in maintaining their self-renewal potential and undifferentiated state. MSCs have been proven to possess immunomodulatory properties and have been used clinically to treat autoimmune diseases. Here, we tested the effects of hypoxia on the immunomodulatory properties of MSCs and examined its possible underlying mechanisms. We found that hypoxic stimulation promoted the immunomodulatory properties of human ging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 35 publications
1
55
0
Order By: Relevance
“…As described previously, hypoxia stimulates the differentiation of dental stem cells . Hypoxia has also been reported to stimulate the immunosuppressive functions of gingival stem cells . This study demonstrates that the inflammatory response in gingival epithelial cells is under regulation by hypoxia‐induced HIF‐1α.…”
Section: Discussionsupporting
confidence: 80%
“…As described previously, hypoxia stimulates the differentiation of dental stem cells . Hypoxia has also been reported to stimulate the immunosuppressive functions of gingival stem cells . This study demonstrates that the inflammatory response in gingival epithelial cells is under regulation by hypoxia‐induced HIF‐1α.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, GMSCs can be easily expanded ex vivo for cell-based clinical applications but may be restricted in their applications. Furthermore, GMSCs have also been reported to possess immunomodulatory capabilities, comparable to other MSC-like populations [37,52]. GMSCs suppressed PBMNC proliferation and enhanced the expression of IL-10, IDO, inducible nitric oxide synthase, and cyclooxygenase 2, all of which are immunosuppressive factors, in response to stimulation with the inflammatory cytokine, IFN-γ.…”
Section: Dental-tissue-derived Stem Cellsmentioning
confidence: 97%
“…Systemic infusion of GMSCs into an experimental colitis mouse model significantly ameliorated both the clinical and histopathological severity of the colonic inflammation mediated by the suppression of inflammatory infiltrates and inflammatory cytokine expression and inhibited regulatory T cell infiltration and IL-10 expression at the colonic sites [37]. Another study revealed that systemic infusion of hypoxiastimulated GMSCs into an excisional skin-wound-healing mouse model enhanced wound repair mediated by the suppression of inflammatory cells and pro-inflammatory cytokine expression, and an increase in IL-10 expression [52]. Although further studies are needed, GMSCs could be an attractive cell source for promoting tissue regeneration and recovery in autoimmune and inflammatory diseases.…”
Section: Dental-tissue-derived Stem Cellsmentioning
confidence: 98%
“…This mechanism also existed in the hypoxic environment [102]. In addition, human GMSCs have elicited M2 polarization of macrophages, which may contribute to rapid reepithelialization, improvement of angiogenesis, and tissue remodeling of skin wound [101].…”
Section: Mscs Derived From Other Tissuesmentioning
confidence: 99%